2002
DOI: 10.1046/j.1532-5415.2002.t01-1-50302.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Determinants of Outcome After Acute Myocardial Infarction: A Dobutamine‐Atropine Stress Echocardiographic Study

Abstract: DASE was more predictive of outcome than clinical data and resting echocardiography in both age groups. Scar size and remote wall motion abnormalities were the primary determinants of outcome irrespective of age. The worse prognosis of older patients correlated with diabetes mellitus, greater scar size, and higher incidence of remote inducible ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In previous analyses, patients treated with PCI underwent DSE within 10 days from the acute event, to predict the following regional and global contractile recovery [12,13]. In agreement with previous works, we can appreciate a positive relationship between viability in the necrotic area and LV global systolic function: a study by Bolognese et al [14] documents in 93 patients treated with PCI, within 6 h from the acute event, a significantly better LV EF in the group with infarct zone viability.…”
Section: Impact Of Myocardial Viability On LV Efsupporting
confidence: 88%
See 1 more Smart Citation
“…In previous analyses, patients treated with PCI underwent DSE within 10 days from the acute event, to predict the following regional and global contractile recovery [12,13]. In agreement with previous works, we can appreciate a positive relationship between viability in the necrotic area and LV global systolic function: a study by Bolognese et al [14] documents in 93 patients treated with PCI, within 6 h from the acute event, a significantly better LV EF in the group with infarct zone viability.…”
Section: Impact Of Myocardial Viability On LV Efsupporting
confidence: 88%
“…Dobutamine stress echo (DSE) is an established noninvasive diagnostic tool that evaluates myocardial viability and residual ischemia in patients with recent MI [12][13][14], independently of the patient's age.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] In addition, these clinical variables also have been proved to be AKI predictors in cardiovascular patients. [32][33][34][35][36] In the present study, by adjusting the baseline risk factors, inflammatory markers, severity of AMI and treatment in the multivariate analysis, initial eGFR and hs-CRP level on admission were independent predictors for AKI occurrence during the first week of an AMI patient's hospitalization.…”
Section: Hsieh Mj Et Almentioning
confidence: 99%
“…Both female sex and old age have been related to worse prognosis after acute myocardial infarction. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As regards gender, various data suggest that it is not an independent adverse prognosticator, but that it is frequently related to high-risk profile and worse coronary angiographic pattern. 13,14 On the other hand, the reasons why elderly patients have a worse prognosis even after successful reperfusion are not completely clear, and apparently neither larger infarct size nor lower LVEF are involved as causative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous echocardiographic data suggested that elderly patients had a larger infarct zone. 10 However, studies using Tc-99m-sestambi imaging in the thrombolytic era suggested that older patients did not show larger infarct size nor a significantly lower left ventricular ejection fraction (LVEF), although their prognosis was worse than in their younger counterparts. 11,12 As regards gender, it is known that women show a worse prognosis than men, but this is seemingly related to older age, high-risk factor profile, and unfavorable angiographic features and not to an intrinsic adverse prognostic meaning of female sex.…”
Section: Introductionmentioning
confidence: 99%